Nie tylko biurko i pióro – rekwizyty w filmach biograficznych o życiu Jane Austen - Śliwńska, Anna (Przestrzenie Teorii, 2023)
The following text begins with an introduction that discusses (relevant for the subsequent argument) issues related to biotopic and the role of props in the context of the discussed films. The subsequent part of the argument focuses on the significance of props (such as a desk, a quill, a letter, and a book) in Becoming Jane (2007, dir. Julian Jarrold) and Miss Austen Regrets (2008, dir. Jeremy Lovering). The analysis explores the situation where these objects convey specific information encrypted by the directors, while also allowing for viewer interpretations regarding their functions. The text argues that although it is not possible to present the “truth” about the writer’s life, one can still attempt to know and understand her world, and the props depicted in the films play a significant role in this process.